An American Looks At Kairos - Eckardt, A. Roy (Theology today, 1986)
“According to a long-standing Christian tradition relating to oppression, a particular tyrant or a particular tyrannical regime ‘forfeits the moral right to govern and the people acquire the right to resist.’ And this is the state of affairs in today's South Africa… Radical South African liberation thinking-praxis goes much farther than the non-revolutionist Social Gospel tendencies of much American black liberation thinking.”